Interazione tra Campi Elettromagnetici e Biosistemi ICEmB Proceedings del VI convegno nazionale - Lodi, Matteo Bruno; Fanti, Alessandro; Massa, Rita (RESOCONTI, 2022)
The aim of the conference, in line with previous initiatives, was to stimulate discussion among researchers who, in their respective disciplinary fields (physics, engineering, biology, medicine, epidemiology), actively contribute to the development of knowledge in the field of bioelectromagnetism and the interaction between electromagnetic fields and biosystems. Contributions cover the following, but not exclusive, topics: i) study of the effects of electromagnetic fields in vivo, in vitro, on humans (laboratory and/or epidemiological studies), ii) exposure/dosimetry, iii) biomedical applications, iv) interaction mechanisms, and v) food engineering.